2020
DOI: 10.2147/ijn.s198914
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optimization of Processing Parameters of Nanoemulsion Containing Aripiprazole Using Response Surface Methodology</p>

Abstract: Background: Aripiprazole, which is a quinolinone derivative, has been widely used to treat schizophrenia, major depressive disorder, and bipolar disorder. Purpose: A Central Composite Rotatable Design (CCRD) of Response Surface Methodology (RSM) was used purposely to optimize process parameters conditions for formulating nanoemulsion containing aripiprazole using high emulsification methods. Methods: This design is used to investigate the influences of four independent variables (overhead stirring time (A), sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The quadratic polynomial model is illustrated in Table 2 . The p -value (<0.0001) indicated that the developed model was significant and adequate to demonstrate the actual interaction between the significant variables and the response (hydroxyl value) [ 36 ]. The lack of fit ( F -value = 4.18) showed insignificant data, which was comparative to the pure error of the experiments, which indicated that the quadratic model data were convenient to depict the whole experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The quadratic polynomial model is illustrated in Table 2 . The p -value (<0.0001) indicated that the developed model was significant and adequate to demonstrate the actual interaction between the significant variables and the response (hydroxyl value) [ 36 ]. The lack of fit ( F -value = 4.18) showed insignificant data, which was comparative to the pure error of the experiments, which indicated that the quadratic model data were convenient to depict the whole experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…21 Several approaches have been made by different researchers to improve the delivery of ARP. Some of the recent approaches involve the development of mixed micellar delivery to improve solubility and oral bioavailability of ARP, 22 the development strategy of ARP NE using response surface software, 23 and the nose-to-brain delivery approach of ARP using the poly(caprolactone) nanoparticle platform. 17 Emerging researches provoke this novel research towards an extensive study on planning to develop a safe and effective TPGS based mucoadhesive NE of ARP (ARP-MNE) using Box-Behnken statistical design to target the brain via intranasal administration.…”
Section: Introductionmentioning
confidence: 99%
“…Aripiprazole was approved by the FDA in 2002, and is an atypical third-generation antipsychotic that, opposed to most other antipsychotic drugs, acts as a partial agonist for dopamine D2 receptors and agonist of serotonin 5-HT1A receptors, being reported to be effective against both positive and negative symptoms of schizophrenia [ 36 , 54 ]. Howver, although it has been considered to be comparatively safer than other similar therapeutics, there have been reports of serious systemic side effects (hypotension, hyperglycemia, neuroleptic malignant syndrome, QT interval prolongation), and it has a very low water solubility (predictably 0.00777 mg/mL), which makes it challenging to formulate at high strength [ 35 , 36 , 37 , 54 ]. In order to tackle these issues, Samiun et al and Masoumi et al [ 35 , 36 ] formulated aripiprazole into an O/W nanoemulsion, for intravenous administration.…”
Section: Nanometric Emulsions Containing Antipsychotic Drugsmentioning
confidence: 99%
“…Howver, although it has been considered to be comparatively safer than other similar therapeutics, there have been reports of serious systemic side effects (hypotension, hyperglycemia, neuroleptic malignant syndrome, QT interval prolongation), and it has a very low water solubility (predictably 0.00777 mg/mL), which makes it challenging to formulate at high strength [ 35 , 36 , 37 , 54 ]. In order to tackle these issues, Samiun et al and Masoumi et al [ 35 , 36 ] formulated aripiprazole into an O/W nanoemulsion, for intravenous administration. The nanoemulsion was prepared using high energy emulsification methods, and contained palm kernel oil esters, soybean lecithin (Lipoid S75), Tween ® 80 (polysorbate 80-polyoxyethylene 20 sorbitan monooleate), glycerol and water (specific quantities in Table 8 ).…”
Section: Nanometric Emulsions Containing Antipsychotic Drugsmentioning
confidence: 99%